Paperless SMEs in manufacturing sector - Melecký, Vojtěch (2019)
The goal of this thesis is to propose a solution which drastically reduces use of paper on manufacturing shopfloor in specific application. Competitive pressures force companies to become lean and eliminate ineffective processes, such as paper-based information distribution, to sustain business in the increasingly globalized environment. Following literature review that captures the essence of paperless concept throughout its historical development up to recent time, author enhances summarized knowledge by case study of such transformation and subject matter expert interview that help to further understand challenges of paperless operations among manufacturing small and medium-sized enterprises. Thesis is concluded with application of gained knowledge, where paperless shopfloor is designed in machinery- producing firm.